2022
DOI: 10.1002/fft2.133
|View full text |Cite
|
Sign up to set email alerts
|

Plantain‐based dough meal: Nutritional property, antioxidant activity and dyslipidemia ameliorating potential in high‐fat‐induced rats

Abstract: This study was designed to evaluate the nutritional property of plantain-based dough meal, antioxidant activity and dyslipidemia-ameliorating potential in high-fatinduced rats. The flour blends, that is, plantain 70%, soy cake 30% (PSC); plantain 65%, soy cake 30%, rice bran 5% (PSR); plantain 65%, soy cake 30%, oat-bran 5% (PSO); plantain 60%, soy cake 30%, rice bran 5%, oat-bran 5% (PSRO); and controls (100% plantain flour and Cerolina) were evaluated for proximate, amino acids, antioxidants, phenolic profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 134 publications
1
13
0
Order By: Relevance
“…Crude extracts that form during food processing are considered an alternative source of antioxidants for improved management and prevention of metabolic diseases associated with oxidative stress ( 54 , 55 ). The major antioxidants found in plant extracts are phenolic compounds, which include phenolic acids, flavonoids, and anthocyanins ( 47 ).…”
Section: Plant-based Functional Foods With Antioxidant Effectsmentioning
confidence: 99%
“…Crude extracts that form during food processing are considered an alternative source of antioxidants for improved management and prevention of metabolic diseases associated with oxidative stress ( 54 , 55 ). The major antioxidants found in plant extracts are phenolic compounds, which include phenolic acids, flavonoids, and anthocyanins ( 47 ).…”
Section: Plant-based Functional Foods With Antioxidant Effectsmentioning
confidence: 99%
“…Bifidobacterium can improve glucose tolerance in people with hyperglycemia or other metabolic disorders ( Ming et al, 2021 ). Many studies have reported that the metabolic diseases were improve by regulating intestinal flora with natural active substances ( Li et al, 2018 ; Oluwajuyitan et al, 2022 ; Wan et al, 2018 ; Yang et al, 2022 ). Therefore, research on health effects of gut microbiota is of considerable importance.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Hence, for the sake of human health, alternative therapies are urgently required to lower low-density lipoprotein cholesterol (LDL-c) to realize the effective manipulation of hyperlipidemia. 6,7 In recent years, the interaction mechanism between the gut microbiome and hyperlipidemia has been revealed. The gut microbiota is a constellation of microbial species with tremendous biotransformation capabilities; its structure and quantity reflect the exquisite modulation of host metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Because of extremely high abuse potential and noticeable chronic side effects in statin therapy, they are restricted under certain circumstances 4,5 . Hence, for the sake of human health, alternative therapies are urgently required to lower low‐density lipoprotein cholesterol (LDL‐c) to realize the effective manipulation of hyperlipidemia 6,7 …”
Section: Introductionmentioning
confidence: 99%